HUBUNGAN JENIS KELAMIN DAN UANG SAKU DENGAN TINGKAT DEPRESI PADA MAHASISWA BARUPERGURUAN TINGGI NEGERI DI BANYUWANGI - Bagas Aidi; Ajeng Febriyanti R; Meirna Mega R; Ayik Mirayanti Mandagi (Journal of Community Mental Health and Public Policy)
ABSTRACT Depression is a disease characterized by prolonged sadness and loss of interest in activities that we normally do happily. A freshman is someone who is moving towards personal maturity and is still in transition, freshmen are very susceptible to increased depression. The purpose of this study was to analyze the relation between gender and pocket money with depression levels. This research was an analytical study used a cross sectional study. The data was collected online by distributing the questionnaire link to 110 students. The results of this study was indicate that the largest number of students were women, the maximum amount of pocket money among students was Rp. 500,000 - Rp. 1,000,000. minimum> Rp. 1,000,000.00. Based on the results of statistical tests used the Chi-square test data obtained Ï = 0.068. The value of Ï obtained was more than 0.05, meaning that there was no relationship between pocket money and the level of depression. Between sex and the level of depression, the data obtained Ï = 0.091, the value of Ï obtained was greater than 0.05, meaning that there was no significant relationship between gender and depression levels in new students. The conclusion ofthis study is that there was no significant relationship between gender and the level of depression in freshmen. There was no significant relationship between the allowance factor and the level of depression in new students. Keywords: New Students, Depression, Gender, Allowance.